(untitled) (Heritage, 2020)
Higher Education reform and modernization processes in Serbia were initiated by the overall `Europe of knowledge` project, which encompassed Bologna and Lisbon declarations aiming to enroll Western Balkan countries into unique European Higher Education Area. By the adoption of the Law on Higher Education in 2005, these processes obtained their legal ground in Serbia and regulated implementation of the principles of both declarations, while Tempus (Trans-European Mobility Programme for University Studies) as the European Union programme for reform and modernization of Higher Education additionally supported internationalization of Higher Education Institutions in Serbia and harmonization of their curricula with highest European educational standards. This essay gives an overview on development of Tempus programme at the University Pristina temporarily settled in Kosovska Mitrovica since 2009, when the university for the first time applied for this kind of donation until its official closure and completion of implementation of all its projects where university was involved.